2018
DOI: 10.3892/ijmm.2018.3610
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor regulates marmoset induced pluripotent stem cell proliferation via a PI3K/‌Akt‑dependent Tbx‑3 activation pathway

Abstract: Leukemia inhibitory factor (LIF) is the most pleiotropic cytokine of the interleukin-6 family, and is widely used to establish and maintain pluripotent stem cells, particularly mouse pluripotent stem cells. However, no reports have fully elucidated the application of LIF in marmoset induced pluripotent stem cell (iPSC) culture, particularly the underlying mechanisms. To demonstrate the feasibility of the application of LIF to marmoset iPSCs, the present study assessed these cells in the presence of LIF. Cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…6). These data was in line with previous ndings that miR-29 was expressed during active pulmonary tuberculosis [23], while miR-23, miR-29, miR-145, and miR -452 were either up-or downregulated in chronic obstructive pulmonary disease (COPD), non-small cell lung cancer (NSCLC) and in ammatory responses [24][25][26][27].…”
Section: Conserved Mirnassupporting
confidence: 91%
“…6). These data was in line with previous ndings that miR-29 was expressed during active pulmonary tuberculosis [23], while miR-23, miR-29, miR-145, and miR -452 were either up-or downregulated in chronic obstructive pulmonary disease (COPD), non-small cell lung cancer (NSCLC) and in ammatory responses [24][25][26][27].…”
Section: Conserved Mirnassupporting
confidence: 91%
“…AKT activation enhances the reprogramming of somatic cells into iPSCs [2022], and our study showed that overexpression of PBX1 activated the AKT/GSK3β signaling pathway, suggesting a role for PBX1 in reprogramming of HF-MSCs into HF-iPSCs. Indeed, the qPCR analysis showed that endogenous PBX1 levels increased with time during HF-iPSC reprogramming induced by SOMK transduction (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…AKT activation can upregulate glucose transporters and metabolic enzymes involved in glycolysis, thereby enhancing the generation of iPSCs from human somatic cells [19, 20]. In the primate iPSC pluripotency network, the AKT pathway significantly upregulates T-box 3, a known transcriptional repressor that interacts with the pluripotency factors NANOG and OCT4 to promote the maintenance of pluripotency [21, 22]. Moreover, the AKT/GSK3β pathway is involved in β-catenin phosphorylation and regulates β-catenin to affect ubiquitin-mediated protein degradation.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Previously, TBX3 as another member of TBX family was found to be associated with the PI3K/AKT pathway. 22 Moreover, it is demonstrated that TBX1 functions as a tumor suppressor in thyroid cancer by inhibiting activation of the PI3K/AKT pathway. 23 Therefore, we speculated that TBX5-AS1 might participate in NSCLC progression through the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%